The secret Sankara : on multivocality and truth in Sankara's teaching - Grinshpon, Yohanan, 1948- (Jerusalem studies in religion and culture ;, 2011)
This book offers a new perception and reading of one of the most well-known documents of Indian philosophy and theology, Sankara's Brahmasutrabhasya. the author's presentation of the self as a subject free of any trace of (disturbungly real) objectivity recieves a fresh explication.